PENGARUH KOMPETENSI GURU TERHADAP MOTIVASI BELAJAR SISWA (STUDI SURVEI DI SDI AL AKHYAR JAKARTA TIMUR) - Nawawi, Abdul Aziz; Ulfah, Maria; Kunaenih; Affaf Rizqillah, Mochammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by differences in students' learning motivation levels at SDI Al-Akhyar, East Jakarta. Teacher competence, comprising pedagogical, professional, personal, and social competence, was assumed to be one of the factors influencing this condition, since teachers who master these competencies are expected to create a conducive learning atmosphere that fosters students' motivation to learn. This study aimed to determine whether teacher competence has an influence on students' learning motivation at SDI Al-Akhyar, East Jakarta. A quantitative approach with a descriptive-correlational survey method was used. The population consisted of all fourth- and fifth-grade students, from which a sample of 60 students was selected through purposive sampling. Data were collected through questionnaires, observation, interviews, and documentation, and were analyzed using the Pearson Product Moment correlation technique and the coefficient of determination with the assistance of IBM SPSS Statistics. The results showed a positive and significant influence of teacher competence on students' learning motivation, with a correlation coefficient (r) of 0.816, categorized as a strong relationship, and a coefficient of determination (R Square) of 0.666, indicating that teacher competence contributed 66.6% to students' learning motivation while the remaining 33.4% was explained by other factors outside this study. Based on these findings, the alternative hypothesis (Ha) was accepted and the null hypothesis (H0) was rejected, meaning that the better the competence demonstrated by teachers, the higher the students' learning motivation.